2012
DOI: 10.1177/0271121412467074
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Paraeducators to Support the Communication of Young Children With Complex Communication Needs

Abstract: Paraeducators are frequent communication partners for young children with complex communication needs (CCN) in early childhood settings. This study examined the impact of instruction to paraeducators in two communication interaction strategies (IPLAN [Identify activities for communication, Provide means for communication, Locate and provide vocabulary, Arrange environment, use iNteraction strategies] and MORE [Model AAC, Offer opportunities for communication, Respond to communication, Extend communication]) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 31 publications
4
46
0
2
Order By: Relevance
“…Large effects of intervention were found on partner's strategy use in three of four reading studies (see Table 1) and at followup, while small effects on fidelity of mass trial teaching were reported (Chang, 2009). Furthermore, when fidelity of (Douglas et al, 2012;Ganz et al, 2013;Stiebel, 1999), while Cafiero (1995) found moderate effects for partner communication frequency. Finally, Romski et al (2010) found small effects for communication turn frequency and no effects for parent MLU or mean turn length.…”
Section: Communication Partner Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Large effects of intervention were found on partner's strategy use in three of four reading studies (see Table 1) and at followup, while small effects on fidelity of mass trial teaching were reported (Chang, 2009). Furthermore, when fidelity of (Douglas et al, 2012;Ganz et al, 2013;Stiebel, 1999), while Cafiero (1995) found moderate effects for partner communication frequency. Finally, Romski et al (2010) found small effects for communication turn frequency and no effects for parent MLU or mean turn length.…”
Section: Communication Partner Outcomesmentioning
confidence: 99%
“…Novel protocols referred to as "naturalistic" (Cafiero, 1995;Nunes & Hanline, 2007) consisted of modeling communication behaviors as well as prompting (1) SGD (2) Yes (1) TACL-3 SS 106-109 (106) Intervention-1 large Douglas, Light, and McNaughton (2012) and Ganz et al (2013) used play routines as the context to elicit communication opportunities. In addition, Chang (2009) used a mass trial learning approach (repeated sets of teaching trials), whereas Stiebel (1999) applied a home routine problem-solving intervention.…”
Section: Book Readingmentioning
confidence: 99%
“…Thus, the strategies outlined in the previous paragraph about IPE are critical for promoting instruction and communication facilitation with multiple “teachers” and across multiple environments. Classroom teachers and school personnel have become more effective communication partners (Douglas, Light & McNaughton, 2012; Kent-Walsh & McNaughton, 2005; Kent-Walsh, Stark, & Binger, 2008). Studies have also shown that parents, siblings, and caregivers can be effective communication partners and teachers across the lifespan (Cheslock, Barton-Hulsey, Romski, & Sevcik, 2008; Skotko, Koppenhaver, & Erickson, 2004).…”
Section: Intervention Guidancementioning
confidence: 99%
“…Pesquisadores sugeriram a necessidade de mais pesquisas para fomentar a utilização da comunicação suplementar e alternativa ao nível da Educação Infantil, incluindo investigações para promover interações entre pares (Barker et. al, 2013;Mcnaughton;Light, 2013).…”
Section: Conclusõesunclassified